Choriocarcinoma on hysterectomy specimen in Senegal: histological study - Ndiade, Amadou; Gaye, Abdou M.; Sy, Mama; Thiam, Ibou; Diop, Ndiaga; Gueye, Mame V.; Diatta, Robert; Diatta, Ange L.; Senghor, Fabrice; Faye, Oumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Trophoblastic diseases are in general exclusive to women in their reproductive years. Gestational choriocarcinoma (GC) is a rare malignant tumor derived from the trophoblast of women in childbearing age. Our objective was to study the epidemiological and clinicopathologic aspects at the laboratories of pathological anatomy and cytology (ACP) of Aristide Le Dantec Hospital and General Idrissa Pouye Hospital. Methods: Our study was conducted in the anatomy and pathology laboratories of the Hôpital Général Idrissa Pouye and the Hôpital Aristide Le Dantec in Dakar. This study was based on records of pathological reports of gestational choriocarcinomas from these different laboratories. This was a retrospective and descriptive bi-centric study, spread over eight (8) years from January 1, 2013, to December 31, 2020. All cases diagnosed on hysterectomy specimens and with a formal conclusion of choriocarcinoma have been included. We recorded the data collected in Excel 2007 software and the analysis was made using Epi Info. Results: We collected 25 cases of choriocarcinomas. The mean age of the patients was 38.1±9.7. Mixed seat tumors (intra-cavitary and intra-mural) were the most frequent with 48% of cases. Patients who were at FIGO stage 1 represented for 88% of cases. Conclusions: Gestational choriocarcinoma (GC) is a proliferation of the trophoblast (cytotrophoblast and syncitiotrophoblast). This study has helped establish histopathological data of choriocarcinoma on hysterectomy specimen in Dakar.